Immigration, integration and the labour market: Turkish immigrants in Germany and the Netherlands - Rob Euwals; Jaco Dagevos; Mérove Gijsberts; Hans Roodenburg (Institute for the Study of Labor (IZA), 2007)
On the basis of three micro datasets, the German Socio-Economic Panel 2002, the Dutch Social Position and Use of Provision Survey 2002 and the Dutch Labour Force Survey 2002, we investigate the labour market position of Turkish immigrants in Germany and the Netherlands. We compare labour market outcomes of Turkish immigrants, including both the first and second generation, and natives in both countries by using the Blinder-Oaxaca decomposition method. We find that Turkish immigrants have lower employment rates, lower tenured job rates and lower job prestige scores than natives. In both countries, the lower level of education and the age composition of the Turkish immigrants partly explains the unfavourable labour market position. The standardized gap the gap that remains after correction for the observed individual characteristics - in the employment and tenured job rate remains large for the Netherlands, while the standardized gap in the job prestige score remains large for Germany. Differences in past immigration policies between Germany and the Netherlands are likely to be important for explaining the labour market position of Turkish men in both countries.
urn:nbn:de:101:1-20080414132
Keywords: 330; Türken; Migranten; Berufliche Integration; Ausländische Arbeitskräfte; Erwerbsstatus; Deutschland; Niederlande